2022
DOI: 10.1111/eth.13275
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for general intelligence in a fish

Abstract: The average mammal or bird has a roughly ten times larger brain relative to body size than the average ectotherm vertebrate. It has been surprisingly challenging to determine how this translates into increased cognitive performance. In particular, it is unclear whether the brain size differences translate into qualitative differences in specific cognitive abilities. Here, we provide a first exploratory study to examine the possibility that the larger brains of endotherms support a different organisation of inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…The test assesses basic operant conditioning abilities, and simple cognitive processes are sufficient for forming associations ( Savage 1980 ; Bielecki et al 2023 ; Triki et al 2023a ). The task is often excluded when researchers look into complex cognitive abilities, like the “general intelligence” factor ( Damerius et al 2017 ; Aellen et al 2022 ). In sum, social complexity would unlikely impact how an individual forms basic associations, such as between a color cue and a food reward.…”
Section: Discussionmentioning
confidence: 99%
“…The test assesses basic operant conditioning abilities, and simple cognitive processes are sufficient for forming associations ( Savage 1980 ; Bielecki et al 2023 ; Triki et al 2023a ). The task is often excluded when researchers look into complex cognitive abilities, like the “general intelligence” factor ( Damerius et al 2017 ; Aellen et al 2022 ). In sum, social complexity would unlikely impact how an individual forms basic associations, such as between a color cue and a food reward.…”
Section: Discussionmentioning
confidence: 99%
“…social competence [7], and non-social flexibility are affected similarly by the same physiological manipulation [38]. While previously disputed [39], this provided the first evidence of domain-general cognition in a fish [38]. We propose that our results provide further indication of domain-general cognition in fish spanning the social and non-social domain because TI in a social hierarchy context was shown to exist in the social cichlids A. burtoni and J. transcriptus [5,12], and TI in a non-social context was shown in a social cichlid in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, it was reported that with greater IC performance in the tube task processed social information mostly with the left hemisphere of the brain (Lucon-Xiccato et al 2020d ). In cleaner wrasse, IC measured with the detour task was negatively correlated with performance in a reversal learning task (Aellen et al 2022 ). Reversal learning is usually considered a measure of another executive function, cognitive flexibility.…”
Section: Within-species Variability In Inhibitory Control Of Fishmentioning
confidence: 99%